A Novel Approach to Cybersecurity Threats Classification by its Nature - Pinchuk, Alla; Odarchenko, Roman; Polihenko, Oleh (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
A comprehensive and precise classification framework is vital for understanding and categorizing cyber threats in the rapidly evolving cybersecurity landscape. Many existing classification models fail to adequately address the diverse and dynamic nature of modern threats. This paper proposes a refined approach to classification, focusing on the nature of cyber threats to provide a more accurate and detailed understanding.